Think Pair Share Cooperative Method Promotes Elementary Indonesian Language Learning Interest: Metode Kooperatif Think Pair Share Mendorong Minat Belajar Bahasa Indonesia Sekolah Dasar - Feronica Indah Sari Topuko; Zulnuraini Zulnuraini; Azizah Azizah; Asriani Asriani; Kasmawati Kasmawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Indonesian language education is fundamental for developing communication and literacy skills within the national curriculum. Specific Background However, fifth-grade students at SDN Doda currently exhibit low attention, involvement, and enthusiasm during instruction, largely due to teacher-centered conventional methods. Knowledge Gap While cooperative pedagogical approaches are widely recognized, specific evidence regarding the application of collaborative frameworks utilizing audiovisual media to address low student engagement in elementary subjects remains limited. Aims This study investigates the application of a targeted collaborative model on student engagement in fifth-grade subjects at SDN Doda. Results Utilizing a Pre-Experimental One Group Pretest-Posttest Design with 16 pupils, the analysis revealed a statistically significant difference (Sig. 2-tailed of 0.002 < 0.05), with the mean score rising from 42.25 to 47.06. Novelty This research demonstrates the specific utility of combining a structured interactive syntax with targeted audiovisual stimulus to actively engage elementary pupils in intrinsic story elements. Implications These findings suggest that providing structured opportunities for independent thought, paired discussion, and public sharing serves as a highly supportive alternative pedagogical strategy for fostering active classroom participation and sustained engagement. Highlights Pre-test and post-test assessments of fifth-graders revealed a statistically significant score progression from 42.25 to 47.06. The applied pedagogical strategy successfully stimulated active classroom participation during intrinsic story element lessons. Data analysis utilizing paired sample t-tests confirmed a significance value of 0.002, verifying positive instructional outcomes. Keywords Think Pair Share; Cooperative Learning; Learning Interest; Indonesian Language; Elementary School